2022
DOI: 10.1002/jnr.25028
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of brain activity and structural network in multiple sclerosis: A graph frequency analysis study

Abstract: The brain activities and the underlying wiring diagrams are vulnerable in multiple sclerosis (MS). Also, it remains unknown whether the complex coupling between these functional and structural brain properties would be affected. To address this issue, we adopted graph frequency analysis to quantify the high‐order structural‐functional interactions based on a combination of brain diffusion and functional MRI data. The structural‐functional decoupling index was proposed to measure how much brain regional functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In particular, the disruption of the DMN network’s connections can result in the decoupling phenomenon associated with cognitive decline [ 49 , 50 ]. Reductions in SC and FC in the SOM network in MCI patients were associated with decreased cognitive control function [ 4 , 51 ] and deterioration of working memory, attention, and arithmetic skills [ 52 ]. Other studies revealed that cognitively impaired individuals showed abnormalities in the VIS network [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the disruption of the DMN network’s connections can result in the decoupling phenomenon associated with cognitive decline [ 49 , 50 ]. Reductions in SC and FC in the SOM network in MCI patients were associated with decreased cognitive control function [ 4 , 51 ] and deterioration of working memory, attention, and arithmetic skills [ 52 ]. Other studies revealed that cognitively impaired individuals showed abnormalities in the VIS network [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the structural-decoupling index is proposed to quantify the regional coupling strength between structure and function 12 , revealing a meaningful sensorimotor-to-association gradient 23 , 24 across the neocortex in humans. The structure-function coupling based on GSP has promising directions in task decoding 25 , individual fingerprinting 25 , and brain dysfunction 26 28 . However, given the inherent limitations of dMRI tractography in examining anatomical connections 29 , 30 , the degree to which structural connectivity constrains functional activity remains largely uncharted.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the structural-decoupling index was proposed to quantify the regional coupling strength between structure and function 15 , revealing a meaningful 'sensory-fugal' gradient 24,25 across the neocortex in humans. The structure-function coupling based on GSP has promising directions in task decoding, individual fingerprinting 19 , and brain dysfunction [26][27][28] . However, given the inherent limitations of dMRI tractography in examining anatomical connections 29,30 , the degree to which structural connectivity constrains functional activity remains largely uncharted.…”
Section: Introductionmentioning
confidence: 99%